Harris v Fitzherbert: Customary Rights of Labour on a Shore Whaling Station - Anderson, Stuart (Victoria University of Wellington Law Review, 2011)
This note considers an early adaptation of common law to conditions on New Zealand whaling stations, made relatively easy by the law’s prior acceptance of local custom or usage as a determinant of legal rights. The case, Harris v Fitzherbert from 1843, is significant also for the jury’s acceptance of a manual workers’ construction of the rule over financiers.